The Essence of the Principles of Ukrainian Law in Modern Jurisprudence - LEHEZA, Yevhen; Karina PISOTSKA; Oleksandr DUBENKO; Oleksandr DAKHNO; Artur SOTSKYI (Revista Jurídica Portucalense, 2023)
The purpose of the research is to highlight methodological approaches to understanding principles of law in the contextof modern globalization transformations. Main content. Their ontological, epistemological and axiological nature are revealed, in particular, links of the principles of law with human existence, science and other ways of world perception are being traced. Methodology: The methodological basis of the research is the dialectical method of scientific knowledge, through the application of this method considered were legal, functional, organizational and procedural aspects of methodological approaches to understanding of principles of law in the context of modern globalization transformations. Conclusions. The classification of the principles of law was singled out and a brief description of their types — universal principles, civilizational principles, and right-family principles and possibilities of separating principles of the national legal system was provided.